Tradisi Perjodohan Pilihan Kiai Dalam Prespektif Hukum Islam - M Tajus Syarof; Ahmad Ubaidi Hasbillah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Within the Fathul Ulum Kwagean Pare Kediri Islamic boarding school, there is a tradition that has been maintained and is still in practice today, namely the tradition of arranged marriages among students at the Islamic boarding school. This research aims to analyze the traditions and perspectives of Islamic law regarding matchmaking chosen by Kiai at the Fathul Ulum Kwagean Kediri Islamic boarding school. The type and research approach used is descriptive qualitative. Data collection techniques in this research are observation, interviews and documentation. The data analysis techniques used are data classification, data reduction, data description and conclusions. Meanwhile, testing the validity of the data used is triangulation. The results of this research are (1) The tradition of matchmaking chosen by Kiai at the Fathul Ulum Kwagean Islamic Boarding School in Kediri consists of several aspects, the first of which is universal, namely from the hadith of choosing a soul mate in terms of (religion, lineage, wealth, beauty). Then secondly, Kiai has his own Javanese calculation, and thirdly based on the results of istikharah (2) The perspective of Islamic law on the matchmaking tradition chosen by Kiai at the Fathul Ulum Islamic Boarding School Kwagean Kediri based on Law No.1 of 1974 is clear that Islamic Law and the Marriage Law It does not prohibit if the marriage takes place through a matchmaking process of the Kiai's choice, the marriage is declared valid.